Pengaruh Manajemen Laba Efisien Terhadap Nilai Perusahaan Dengan Rasio Profitabilitas - Dedie Wijaya (Studi Akuntansi dan Keuangan Indonesia, 2017)
The purpose of this research is to estimate whether Efficient Earnings Management will affect the company’s value by using Accounting Performance Analysis ratio as a moderating variable. The presence of Earnings Management misleads investors into producing an incorrect fundamental analysis of a company which effects on the company’s value. The methodological tools to estimate earnings management are Kasznik models (1999) which refer to Siregar and Utama’s research (2008). This research-based on research toward a company that is listed in Jakarta Stock Exchange from 2000 to 2014. The results of this research are proven that there are a positive correl Management and Company’s Values, therefore the presence of the Efficient Earning Management will increase the value of a company. Keywords: Efficient Earnings Management, Company’s Value, Accounting Performance Analysis https://doi.org/10.21632/saki.1.1.54-71